Language Error in Public Spaces: Evidence from Palu City - Suparni, Suparni (Yayasan Kyadiren, 2024)
This study examines errors in Indonesian usage in public spaces in Palu City, focusing on non-standard language, grammatical inaccuracies, spelling, and punctuation. Using a qualitative descriptive method, data were collected through observation and documentation, analyzed with Krippendorf's content analysis model. The findings reveal 69 errors, including 40 prefix, 15 suffix, 10 preposition, 3 title, and 1 word usage errors. The most frequent issue was incorrect